Pulmonary blastomycosis on autopsy: a rare case report - Rana, Shweta; Sharma, Puja; Satarkar, Rahul N.; Kalhan, Shivani; Garg, Shilpa (International Journal of Research in Medical Sciences, 2017)
A case of pulmonary blastomycosis on autopsy in a middle aged male from rural background is presented herewith. Blastomycosis is a pyogranulomatous disease caused by the dimorphic fungus blastomyces dermatitidis. Blastomycosis is endemic in regions of North America that border the Great Lakes. It is one of the great mimickers in medicine. Pulmonary blastomycosis has a broad range of clinical presentations, varying from completely asymptomatic pulmonary infiltrates to diffuse and massive parenchymal involvement that can lead to Acute Respiratory Distress Syndrome (ARDS). Human infection occurs when soil containing microfoci of mycelia is distributed and airborne conidia are inhaled. If natural defences in the alveoli fail to contain the infection, lymphohematogenous dissemination ensues. Diagnosis is based on culture and direct visualization of round, multinucleated yeast forms that produce daughter cells from a single broad- based bud. Most of the cases of blastomycosis reported in India are imported from the endemic areas of the World except a few authochthonous cases in North India.